Biogenic calcium carbonate as evidence for life - S. Ronca; F. Mura; M. Brandano; A. Cirigliano; F. Benedetti; A. Grottoli; M. Reverberi; D. F. Maras; R. Negri; E. Di Mauro; T. Rinaldi (Biogeosciences, 2023)
The history of the Earth is a story of the co-evolution of minerals and microbes: not only have numerous rocks arisen from life but also life itself may have formed from rocks. To understand the strong association between microbes and inorganic substrates, we investigated the moonmilk, a calcium carbonate deposit of possible microbial origin, occurring in the Iron Age Etruscan necropolis of Tarquinia, in Italy. These tombs provide a unique environment where the hypogeal walls of the tombs are covered by this speleothem. To study moonmilk formation, we investigated the bacterial community in the rock in which the tombs were carved: calcarenite and hybrid sandstone. We present the first evidence that moonmilk precipitation is driven by microbes within the rocks and not only on the rock surfaces. We also describe how the moonmilk produced within the rocks contributes to rock formation and evolution. The microbial communities of the calcarenite and hybrid sandstone displayed, at the phylum level, the same microbial pattern of the moonmilk sampled from the walls of the hypogeal tombs, suggesting that the moonmilk originates from the metabolism of an endolytic bacterial community. The calcite moonmilk is the only known carbonate speleothem on Earth with undoubted biogenic origin, thus representing a robust and credible biosignature of life. Its presence in the inner parts of rocks adds to its characteristics as a biosignature.